Phymaturus Wiliamsi: Predator-Prey Interaction - Fava, Gustavo Alfredo (2018)
Predation is a selective force that models prey populations (Sih et al. 1985. Annu. Rev. Ecol. Syst. 16:269–311). However, predator-prey interactions are rarely observed in the field for a given species. The Andean lizard Phymaturus williamsi (Lobo et al. 2013. Zootaxa 3683:117–132), was recently categorized as vulnerable (Abdala et al. 2012. Cuad. Herpetol. 26:215–248) and is endemic to Quebrada Vallecito (31.1791°S, 69.7092°W, WGS 84; 3000 m elev.), in the high Andes, 40 km NW of Calingasta, San Juan Province, Argentina...